2013
DOI: 10.1111/pde.12251
|View full text |Cite
|
Sign up to set email alerts
|

Familial Papular Epidermal Nevus with “Skyline” Basal Cell Layer

Abstract: Papular epidermal nevus with "skyline" basal cell layer (PENS), a novel keratinocytic nevus, has recently been described as a mosaic condition with varying presentations. We herein describe typical PENS lesions, which usually occur sporadically, affecting two members of the same family. The concept of paradominant inheritance is proposed to explain the paradox of occasional transmission of normally sporadically occurring traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
(5 reference statements)
0
15
0
1
Order By: Relevance
“…Five of these developed lesions soon after birth, and in the three remaining cases, the exact age at appearance of the lesions was not mentioned. The number of lesions was variable (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Eight patients (42%) had extracutaneous findings, mainly mild developmental or psychomotor delay.…”
Section: Torrelo Et Almentioning
confidence: 99%
“…Five of these developed lesions soon after birth, and in the three remaining cases, the exact age at appearance of the lesions was not mentioned. The number of lesions was variable (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Eight patients (42%) had extracutaneous findings, mainly mild developmental or psychomotor delay.…”
Section: Torrelo Et Almentioning
confidence: 99%
“…Les lésions sont congénitales ou apparaissent avant l'âge de 3 mois. Elles surviennent généralement de façon sporadique mais une atteinte familiale de premier degré est mentionnée dans deux observations [1,5]. L'hamartome PENS se caractérise par de petites plaques centimétriques en nombre variable (1 à 18), siégeant avec prédilection sur les membres, parfois sur le tronc, le visage ou le cou.…”
Section: Discussionunclassified
“…Tadini et al described two siblings with PENS, one with isolated skin lesions and the other with combined neurologic disorders. A report by Brena et al included a mother and son with isolated skin manifestations. Recently, Zahn et al reported 2 brothers with cutaneous PENS lesions and neurologic symptoms only in the younger brother.…”
Section: Discussionmentioning
confidence: 99%